The Tactile-Visual Conflict Processing and Its Modulation by Tactile-Induced Emotional States: An Event-Related Potential Study - Guo, Chengyao; Dupuis-Roy, Nicolas; Jiang, Jun; Xu, Miaomiao; Xiao, Xiao (Frontiers in Psychology, 2021)
This experiment used event-related potentials (ERPs) to study the tactile-visual information conflict processing in a tactile-visual pairing task and its modulation by tactile-induced emotional states. Eighteen participants were asked to indicate whether the tactile sensation on their body matched or did not match the expected tactile sensation associated with the object depicted in an image. The type of tactile-visual stimuli (matched vs. mismatched) and the valence of tactile-induced emotional states (positive vs. negative) were manipulated following a 2 × 2 factorial design. Electrophysiological analyses revealed a mismatched minus matched negative difference component between 420 and 620 ms after stimulus onset in the negative tactile-induced emotional state condition. This ND420-620 component was considered as a sign of the cross-modal conflict processing during the processing of incongruent tactile-visual information. In contrast, no significant mismatched minus matched negative difference component was found in the positive tactile-induced emotional state condition. Together, these results support the hypothesis that a positive emotional state induced by a positive tactile stimulation improves tactile-visual conflict processing abilities.